Baryon stopping as a relativistic Markov process in phase space - Hölck, Johannes; Wolschin, Georg (Physical review research, 2020)
We reconsider baryon stopping in relativistic heavy-ion collisions in a nonequilibrium-statistical framework. The approach combines earlier formulations based on quantum chromodynamics with a relativistic diffusion model through a suitably derived fluctuation-dissipation relation, thus allowing for a fully time-dependent theory that is consistent with QCD. We use an existing framework for relativistic stochastic processes in spacetime that are Markovian in phase space, and adapt it to derive a Fokker-Planck equation in rapidity space, which is solved numerically. The time evolution of the net-proton distribution function in rapidity space agrees with stopping data from the CERN Super Proton Synchrotron and the BNL Relativistic Heavy Ion Collider.